Hepatitis a virus genotypes and strains from an endemic area of Europe, Bulgaria 2012–2014 - Bruni, Roberto (BMC Infect Dis, 2017)
BACKGROUND: Hepatitis A virus (HAV) infection is endemic in Eastern European and Balkan region countries. In 2012, Bulgaria showed the highest rate (67.13 cases per 100,000) in Europe. Nevertheless, HAV genotypes and strains circulating in this country have never been described. The present study reports the molecular characterization of HAV from 105 patients from Bulgaria. METHODS: Anti-HAV IgM positive serum samples collected in 2012–2014 from different towns and villages in Bulgaria were analysed by nested RT-PCR, sequencing of the VP1/2A region and phylogenetic analysis; the results were analysed together with patient and geographical data. RESULTS: Phylogenetic analysis revealed two main sequence groups corresponding to the IA (78/105, 74%) and IB (27/105, 26%) sub-genotypes. In the IA group, a major and a minor cluster were observed (62 and 16 sequences, respectively). Most sequences from the major cluster (44/62, 71%) belonged to either of two strains, termed "strain 1" and "strain 2", differing only for a single specific nucleotide; the remaining sequences (18/62, 29%) showed few (1 to 4) nucleotide variations respect to strain 1 and 2. Strain 2 is identical to the strain previously responsible for an outbreak in the Czech Republic in 2008 and a large multi-country European outbreak caused by contaminated mixed frozen berries in 2013. Most sequences of the IA minor cluster and the IB group were detected in large/medium centers (LMCs). Overall, sequences from the IA major cluster were more frequent in small centers (SCs), but strain 1 and strain 2 showed an opposite relative frequency in SCs and LMCs (strain 1 more frequent in SCs, strain 2 in LMCs). CONCLUSIONS: Genotype IA predominated in Bulgaria in 2012–2014 and phylogenetic analysis identified a major cluster of highly related or identical IA sequences, representing 59% of the analysed cases; these isolates were mostly detected in SCs, in which HAV shows higher endemicity than in LMCs. The distribution of viral sequences suggests the existence of some differences between the transmission routes in SCs and LMCs. Molecular characterization of an increased number of isolates from Bulgaria, regularly collected over time, will be useful to explore specific transmission routes and plan appropriate preventing measures.